Synthesis by native chemical ligation and characterization of the scorpion toxin AmmTx3. Issue 1 (1st January 2019) - Zoukimian, Claude; Meudal, Hervé; De Waard, Stephan; Ouares, Karima Ait; Nicolas, Sébastien; Canepari, Marco; Béroud, Rémy; Landon, Céline; De Waard, Michel; Boturyn, Didier
Graphical abstract: Abstract: The scorpion toxin AmmTx3 is a specific blocker of Kv 4 channels. It was shown to have interesting potential for neurological disorders. In this study, we report the first chemical synthesis of AmmTx3 by using the native chemical ligation strategy and validate its biological activity. We determined its 3D structure by nuclear magnetic resonance spectroscopy, and pointed out that AmmTx3 possesses the well-known CSαβ structural motif, which is found in a large number of scorpion toxins. Overall, this study establishes an easy synthetic access to biologically active AmmTx3 toxin.